Twisted Sectors for Lagrangian Floer Theory on Symplectic Orbifolds - Chen, Bohui; Ono, Kaoru; Wang, Bai-Ling (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
The notion of twisted sectors plays a crucial role in orbifold Gromov-Witten theory. We introduce the notion of dihedral twisted sectors to construct Lagrangian Floer theory on symplectic orbifolds and discuss related issues.